Pengaruh Peran PKN Terhadap Kebudayaan Asing Pada Kebudayaan Indonesia di Kalangan Remaja - Randi, Muhammad Sinar; Ikhwal, Nabil Zauhair; Munthe, Cindy Mei Yana; Ifani, Mutia; Tanjung, Rizki Adinda Azhar (Yayasan Daarul Huda Kruengmane, 2024)
This study examines the influence of the role of Civic Education (Civics Education) on the penetration of foreign cultures into Indonesian culture among adolescents. In the era of globalization, Indonesian teenagers are increasingly exposed to various foreign cultures through social media, entertainment, and direct interaction. This study aims to identify the extent to which Civics Education can shape adolescents’ attitudes and behaviors in dealing with foreign cultural influences and maintaining Indonesian cultural values. The methodology used in this study includes surveys and in-depth interviews with a sample of teenagers from various schools in Indonesia. The results showed that Civics Education plays a significant role in raising adolescents’ awareness of the importance of maintaining national cultural identity. In addition, it was found that adolescents who have a good understanding of Civics Education tend to be more selective in accepting foreign cultural elements, and are better able to filter negative influences that can damage local culture. Overall, this study confirms the importance of strengthening the Civics curriculum in schools as a strategic effort to protect and promote Indonesian culture in the midst of globalization. Thus, it is hoped that Indonesia’s young generation can become agents of change who not only appreciate, but also maintain the nation’s cultural heritage.